Product Development of Sweet Fermented Rice (Khoa-Mak) Supplemented with Red Yeast Rice - Jirasatid, S.; Nopharatana, M. (International Journal of Agricultural Technology, 2018)
A new healthy food product, sweet fermented glutinous rice (Khoa-Mak) supplemented with red yeast rice was developed in this study. Significant source of Loop-Pang (rice starter culture) for Khoa-Mak fermentation were investigated, and effect of supplementation of red yeast rice on quality of Khoa-Mak during storage was further carried out. Total soluble solid (TSS), pH, ethanol content, yeast and mold, total viable count, Escherichai coli, sensory evaluation of sample were determined. Glutinous rice was fermented with various sources of Loog-Pang (Chachoengsao, Chanthaburi, Trad and Prachinburi) at 30°C for 72 hours. Microbial populations in various Loog-Pang sources increased rapidly during fermentation. Rice fermented by Loog-Pang sources from Trad for 48 hours had the highest sensory acceptability by elderly consumers, and contained 0.12% of ethanol, 40°Brix of TSS, pH of 4.2 and less than 3 MPN/g of E. coli. During storage at 4°C for 2 weeks, microbial populations survived at low pH in Khoa-Mak (without red yeast rice, and supplemented with 0.1, 0.2 and 0.3% of red yeast rice). The supplementation of red yeast rice from 0 to 0.3% resulted in the increasing of Monascus pigments concentrations and antioxidative properties in Khoa-Mak (p<0.05). Sensory scores of Khoa-Mak supplemented with 0.3% of red yeast rice were higher than those for other samples, except Khoa-Mak without red yeast rice (p<0.05). The results indicated that Khoa-Mak supplemented with 0.3% of red yeast rice could be a new healthy food product, particularly for elderly consumers.